A novel inhibitor of nuclear factor kappa-B kinase subunit gamma mutation identified in an incontinentia pigmenti patient with syndromic tooth agenesis. (May 2019) - Sun, Shichen; Li, Fang; Liu, Yang; Qu, Hong; Wong, Sing-Wai; Zeng, Li; Yu, Miao; Feng, Hailan; Liu, Haochen; Han, Dong
Highlights: We identified a novel nonsense mutation (c.924C > G; p.Tyr308*) in IKBKG . We describe detailed dental characteristics of syndromic tooth agenesis in an IP patient. The novel mutation (c.924C > G; p.Tyr308*) in IKBKG is pathogenic. Abstract: Objective: To explore the gene mutation in an incontinentia pigmenti (IP) patient with syndromic tooth agenesis. Methods: Long-range polymerase chain reaction (PCR) and Sanger sequencing were used to detect inhibitor of nuclear factor kappa-B kinase subunit gamma ( IKBKG ) mutation in the IP patient. We used the nuclear factor kappa B (NF-κB) reporter gene to assess activation of NF-κB, after transfecting an empty vector, wild-type, or mutant NF-κB essential modulator (NEMO) plasmid into IKBKG -deficient HEK293T cells, respectively. Furthermore, we performed immunoprecipitation and immunoblotting to describe the polyubiquitination of NEMO. Lastly, we detected the interactions between mutant NEMO and I kappa B kinase alpha (IKKα), I kappa B kinase beta (IKKβ), TNF receptor associated factor 6 (TRAF6), HOIL-1-interacting protein (HOIP), hemo-oxidized iron regulatory protein 2 ligase 1 (HOIL-1), and SHANK-associated RH domain interactor (SHARPIN). Results: A de novo nonsense mutation in IKBKG (c.924C > G; p.Tyr308*) was observed. The Tyr308* mutation inhibited activation of the NF-κB pathway by reducing K63-linked polyubiquitination and linear polyubiquitination. The mutant NEMO was not able to interact with TRAF6, HOIL-1, or SHARPIN. Conclusions: We identified a novel nonsense IKBKG mutation (c.924C > G; p.Tyr308*) in an IP patient with syndromic tooth agenesis. This research enriches the mutation spectrum of the IKBKG gene.